The Effectivity of Transmedia Brand Storytelling on Harry Potter Towards Brand Loyalty in Indonesia - Putri, Kintan Andyarmalasari; Fachira, Ira (Journal of Business and Management, 2019)
Transmedia brand storytelling is one of the new creative strategies to control brand message in an engaging way across technology platforms. However, there are limited studies that explain how this method affects brand loyalty. Harry Potter is one of the brand that successfully gained massive success in their world using transmedia storytelling. The fact that after six years of vacuum from producing, Harry Potter still have high excitement from its customer. The objective of this research is to know the effectivity of transmedia awareness to customer engagement and to know the influence of customer engagement in brand loyalty. The research was conducted through an online questionnaire as a tool to collect data with the result total sample of 374 respondents. The author uses path analysis, which has a purpose of explaining the relationship between variables. Based on the calculation, the author found that transmedia awareness gives a significant influence on customer engagement as well as customer engagement brings significant positive influence on building brand loyalty.Moreover, there is a new finding which this research has quasi mediating effect mediation, which means transmedia awareness is already effectively used in Harry Potter. The finding of this research is expected to enhance knowledge about transmedia brand storytelling. The author also creates some recommendation for future research and business owner that will help them to improve their banding strategies.